Perilaku Konsumsi Berkelanjutan (Sustainable Consumption Behavior) di Indonesia: Peran Environmental Concern, Perceived Consumer Effectiveness dan Altruism - A. Nurul Suci Amaliah; Putri Maisara; Saifullah Waspada; Andi Armayani (Universitas Negeri Padang, 2023)
The consumer consciousness and collective actions of the community constitute a primary challenge in striving for environmental conservation and enhancing social well-being as part of the sustainable development goals. One of the efforts to address this challenge is by adopting sustainable consumption behavior (SCB). In general, this research aimed to engage with sustainable development issues at the consumer level. This research specifically adopts the EECB (Ecologically Conscious Consumer Behavior) model measured by the factors of environmental concern (EC), perceived consumer effectiveness (PCE) and altruism (AL. This research used a survey method and collected data from 304 consumers in Indonesia. The results indicate that environmental concern is not a significant factor in predicting ECCB and confirm the gap between environmental concern and consumer actual behaviors also suggesting that Indonesian consumers still struggle to translate their environmental concern into actual action. Meanwhile, the PCE factor is known to influence ECCB significantly. However, altruism was not found to be a moderating factor in the relationship between PCE and ECCB, but instead strengthened the relationship between EC and ECCB.